IMPACT OF GLOBAL MELTDOWN ON DUBAI’S BOOM: AN ANALYSIS OF THE DEBT CRISIS - Alvares, Jolin Claire (2011)
The study carried out is based on the impact of the debt crisis in Dubai. Dubai went into a crisis after the collapse of world markets post recession and the highly discussed financial crisis. For the purpose of my research, qualitative analysis was carried out to figure the reasons behind why Dubai took such a big hit which eventually indebted them towards their competitor state Abu Dhabi. After the analysis of the data and articles, it was found out that Dubai’s major down fall was itself. There was a major lack of transparency which led to a lot of questions being unanswered and highly unrealistic projects being undertaken which could not be financed at that time. Another reason for its down fall may have been the iron cloth on the workings of the government. This was one of my biggest limitations and may have just been the cause of Dubai’s downfall.